Participative school management: A metasynthesis - Francielli Ferreira da Rocha Romero; Vânia de Fátima Matias de Souza; Amauri Aparecido Bássoli de Oliveira (Journal of Physical Education (Maringá), 2025)
School management research focuses primarily on macro-level theorizing about concepts such as leadership. Therefore, to date, there is a gap in the area regarding participatory school management. This article systematically reviewed existing qualitative case studies on participatory school management published in peer-reviewed journals. An electronic search was conducted in the education database — Eric (Educational Resources Information Center), covering the period from 2001 to June 2022. To meet this objective, the adoption of a meta-synthesis of qualitative case studies was used in order to identify possible cause and effect relationships between the constructs: leadership, relationship management and administrative. The results indicate that the principal's ability and willingness to encourage dialogue, as well as his active engagement in building relationships within the school community and his role as leader, are fundamental aspects. The theoretical reference is based on authors such as Libâneo, Lück and Paro. The research detected that, initially, the concept of school management focused only on the administrative aspects of the function, however, this concept has been transforming over time, being approached in a broader way, covering the pedagogical, political and human aspects.